1988
DOI: 10.1080/00913847.1988.11709576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold and Compression on Edema

Abstract: In brief: A 40-minute cooling period was used to treat artificially induced acute inflammatory reactions in human tissue. Results showed no significant change in the volume of the inflammatory reaction at one hour, though a transient attenuation during the first 15 minutes was detected. The addition of mild pressure (10 mm Hg) to mild cooling (range, 15° to 25° C) produced a highly significant reduction in swelling from 15 minutes onward, This effect was sustained as long as swelling was detectable. Pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Ice can also be used as a form of pain relief in tendonosis. Evidence of efficacy is, however, weak 18 19…”
Section: Physiotherapy Considerationsmentioning
confidence: 99%
“…Ice can also be used as a form of pain relief in tendonosis. Evidence of efficacy is, however, weak 18 19…”
Section: Physiotherapy Considerationsmentioning
confidence: 99%
“…heat and cold) may be applied underlines the fact that some of these treatments have little objective basis. Previous work in a human model of soft-tissue injury has shown that cooling alone does not produce a sustained reduction in swelling and that the addition of mild pressure (10-30 mmHg) to the cooling (1 5C) is necessary for any permanent effects to be seen (Sloan et al, 1988). Schmidt et al, (1979), using an experimental rat paw model, also found that cooling alone did not cause a reduction in swelling.…”
Section: Introductionmentioning
confidence: 95%
“…The benefit of cold and compression in reducing swelling and pain has been well established for many years (McMaster and Liddle, 1980;Berman et al, 1988;Sloan et al, 1988;Cohn et al, 1989;Shelbourne and Wilkens, 1990;Healy et al, 1994) and a variety of devices have been designed to deliver controlled cryotherapy with and without added compression (Knight, 1995, Chapter 8), including:…”
Section: Introductionmentioning
confidence: 99%